Inverse Kinematic Analysis and Evaluation of a Robot for Nondestructive Testing Application. (30th September 2015) - Lu, Zongxing; Xu, Chunguang; Pan, Qinxue; Zhao, Xinyu; Li, Xinliang
Abstract : The robot system has been utilized in the nondestructive testing field in recent years. However, only a few studies have focused on the application of ultrasonic testing for complex work pieces with the robot system. The inverse kinematics problem of the 6-DOF robot should be resolved before the ultrasonic testing task. A new effective solution for curved-surface scanning with a 6-DOF robot system is proposed in this study. A new arm-wrist separateness method is adopted to solve the inverse problem of the robot system. Eight solutions of the joint angles can be acquired with the proposed inverse kinematics method. The shortest distance rule is adopted to optimize the inverse kinematics solutions. The best joint-angle solution is identified. Furthermore, a 3D-application software is developed to simulate ultrasonic trajectory planning for complex-shape work pieces with a 6-DOF robot. Finally, the validity of the scanning method is verified based on the C-scan results of a work piece with a curved surface. The developed robot ultrasonic testing system is validated. The proposed method provides an effective solution to this problem and would greatly benefit the development of industrial nondestructive testing.